Perancangan Aplikasi E-Voting pada Pemilihan Ketua Osis Berbasis Mobile - Arsy Kurniawan (PT. SNN MEDIA TECH PRESS, 2023)
E-voting or electronic voting is a way of voting that utilizes electronic tools to facilitate the voting process. E-voting has advantages such as a fast election process, fast vote counting process, real-time vote counting where every incoming vote will be visible on the application, information is more easily accessible, reduces operational costs in conducting elections or voting and minimizes the shortcomings that exist in conventional voting methods. The rapid development of technology and smartphone users, voting by e-voting is certainly very helpful and speeds up the process of an election. The results of the recapitulation of the 6 test criteria that have been carried out obtained the results of the number of answers from respondents have a value of 100% in accordance with testing the functionality of the system using blackbox testing.